(3CfeGW JLGhQ GdYeQGf GdeNWW h ZjQ GdeNWW ai GdbGgQI (B: s (3OQGSI MGdI efWbJi CQV GddhGA h GdegfOSjf (B/ s - (3gfGA LGO eMehOs; (3SMQ YHOGdefYe YWjI (B: s; (3gHg Gddg YUGe Ndjd (B: s ((3GdbGgQI (B: s (3gfGA LGO eMehO (B: s, 2015)
(3jSYi gPG GdHMK Edi GdELGHI Ydi GdYOjO ef GdJSGDdGJ Yf eGgjI h Tcd GdYdGbGJ Hjf GdGfeGW GdYeQGfjI ai GdbGgQI h eOi JCKjQgG Ydi MjR GdJLGhQ Hjf GdGfeGW GdYeQGfjI h cjajI JMOjO CfeGW GdJLGhQ Hjf GdefGWb GdYeQGfjI GdeNJdaI(B: (3HOQGSI GdGfhGY GdeNJdaI ddJLGhQ Hjf GdfeWjf GdYeQGfjf h GdSeGJ GdeejRI dcd fhY jecf JhajQ EWQ eSJOGe ddJfejI GdYeQGfjI GdHjfjI JSGYO Ydi Jbdjd GdahGQb HjfgeG h OeLgeG ai SjGb GdcJdI GdCSGSjI ddbGgQI(B: (3jgOa GdHMK Edi JbOje EWGQ h JUfja LOjO dJYQja GdefGWb HfGAG Ydi MjR GdJLGhQ GdhGbYI ajg HeG jSGge ajeG HYO ai hVY eOGNd ddJfejI GdYeQGfjI GdbGFeI Ydi GdOeL Hjf GdefGWb h Jbdjd GdahGQb HjfgG s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GfeGW JLGhQs; (3GfeGW YeQGfjIs; (3JWhjQ YThGFjGJs